EXPLORING STUDENT AND LECTURER PERSPECTIVES ON ACADEMIC WRITING: A CASE STUDY AT THE CENTRAL UNIVERSITY OF TECHNOLOGY, SOUTH AFRICA - Fredericks, Brenton Grant; Louw, Tsepo Wisdom (Universitas Islam Sumatera Utara (UISU), 2024)
This study explores the perceptions of students and lecturers regarding the Academic Literacy Course (ALC) at the Central University of Technology (CUT), South Africa. Academic literacy encompasses critical skills for effective communication, while academic writing provides a structured framework for presenting ideas, arguments, and research. The study investigates attitudes toward the course's relevance, effectiveness, and its impact on students' academic writing abilities. Using a qualitative approach, data were collected through semi-structured interviews with students who completed the course and lecturers from the Communication Sciences Department. Thematic analysis revealed recurring patterns and insights from participants. Findings indicate that both students and lecturers value academic literacy as essential for academic writing success. Participants highlighted the course’s focus on critical reading, writing, information literacy, and communication skills, expressing predominantly positive opinions. However, a majority of students (90%) and lecturers (80%) emphasized the need for tailored content and additional resources to address specific academic writing challenges. The study provides valuable insights into the strengths and areas for improvement in the ALC. It suggests that a more discipline-specific approach, incorporating relevant terminology and practices, could better align with students' academic needs. Recommendations include redesigning the course to integrate discipline-specific content and adapting it for both in-person and online delivery. These findings have significant implications for curriculum development, offering strategies to enhance the course’s effectiveness in fostering students' academic literacy and writing proficiency.